1999
DOI: 10.1007/s004210050552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on total daily physical activity in elderly humans

Abstract: This study examined the effect of 12 weeks of exercise training on daily physical activity in elderly humans. Training consisted of a weekly group session and an individual session with cardio- and weight-stack machines. A group of 15 subjects served as the exercise group [EXER mean age 59 (SD 4) years], and 7 subjects as the controls [CONT mean age 57 (SD 3) years]. Physical activity and physical fitness were measured before the start of training (T), at week 6 and week 12 (T0, T6, T12 respectively) in EXER, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
179
2
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 23 publications
10
179
2
3
Order By: Relevance
“…Goran and Poehlman 4 speculated that the level of exercise, 3 haweek at 85% VO 2max, was too vigorous and thus fatigued the elderly participants during the remainder of the day. Recently, however, we 5 showed the same compensatory effect of exercise training on nontraining physical activity in elderly subjects, with a training program of only moderate intensity ( $ 40% VO 2max ). It was shown that elderly subjects anticipate the training program by lowering their physical activity even before the exercise training session.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Goran and Poehlman 4 speculated that the level of exercise, 3 haweek at 85% VO 2max, was too vigorous and thus fatigued the elderly participants during the remainder of the day. Recently, however, we 5 showed the same compensatory effect of exercise training on nontraining physical activity in elderly subjects, with a training program of only moderate intensity ( $ 40% VO 2max ). It was shown that elderly subjects anticipate the training program by lowering their physical activity even before the exercise training session.…”
Section: Introductionmentioning
confidence: 67%
“…4,5,13 These studies demonstrated that exercise training in an elderly population results in a compensatory decline of non-training physical activity. Morio et al 13 measured the effect of training on non-training physical activity by using 7 day activity recordings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Again, training induced an increase in AEE and Tracmor output showed no effect of exercise on non-training physical activity. However Meijer et al, 26 examining with Tracmor 2 the effect of a 12-week training program of moderate intensity in Physical activity assessment with accelerometers KR Westerterp elderly subjects, observed an increase in physical activity on training days, which was compensated with a decrease in physical activity on non-training days. Thus, the effect of exercise training on nontraining physical activity seems to be age dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aging is frequently associated with a decrease in physical activity levels and consequently a decline in physical fitness, which may contribute to the development of coronary heart disease, heart attacks, diabetes, hypertension, obesity, osteoporosis and bone fractures and different kinds of cancer (3,4). United States department of health and human services refers that the promotion of regular and daily physical activity is a good strategy to prevent the onset of age-related diseases and disabilities and the risk of many adverse health outcomes and disability conditions (5).…”
Section: Introductionmentioning
confidence: 99%